Validation of developed method by RP-HPLC for estimation of Prasugrelin human plasma and studying the stability of the drugs in plasma - Ashutosh, Kumar S.; Manidipa, Debnath; Seshagiri, Rao J.V.L.N.; Gowri, Sankar D. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
This paper is concern with a reverse phase high performance liquid chromatography (RP-HPLC) bio-analytical method development and validation for Prasugrel in human plasma using photo diode array detector (PDA detector). The HPLC separation was carried out in an isocratic mode on an X-Terra C18 column (4.6 x 150 mm; 5 μm) with a mobile phase consisting of potassium dihydrogen phosphate [pH 3.0] and acetonitrile in the ratio of 30:70 v/v at a flow rate of 1.0 mL/min. The run time was maintained for 5 mins and the detection was monitored at 210 nm. The percentage recovery was found 99.61-100.06 in human plasma. This reveals that the method is quite accurate. The linearity was found 15-40 μg/mL in human plasma. The inter-day and intra-day precision in plasma was found within the limits. The lower limit of quantification (LLOQ) obtained by the proposed method was 0.05 μg/mL. The percentage relative standard deviation (%RSD) obtained for the drug spiked in plasma for stability studies were less than 2 %. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 1, 2017, Page: 65-75